2006
DOI: 10.1590/s0034-71672006000200020
|View full text |Cite
|
Sign up to set email alerts
|

A construção de uma nova forma de representação profissional: um desafio no "Projeto Político-Profissional da Enfermagem Brasileira"

Abstract: This article is a reflection about the form of Brazilian nursing professional organization, highlighting the limits of the current model and the challenges for the future. It is based on the authors' analysis of an important social movement of Brazilian Nursing, the "Participation Movement" that took place from 1980 to 1990. This Movement has promoted a reflection about nursing work and organization and about nursing participation in the country's re-democratization, as well as defending the right to health. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
(5 reference statements)
0
6
0
1
Order By: Relevance
“…Analyzing the objects of study of the selected articles, it was found that, in the Brazilian context, ABEn was the focus of most of the studies, perhaps because it is the oldest nursing organization in the country, and even acts as an umbrella organization for other municipal, union, and scientific nursing organizations in Brazil (9,11,14) . It seems that, in a way, all of the articles addressed the contributions of the Association to the world of nursing, especially in the areas of education (15)(16) , care and professional practice (14,(17)(18) , political participation (19) , and preservation of the memory of the profession (13) . It is noteworthy that there was mention of unions, specialties, and supervisory bodies of professional nursing practice during the joint work developed by these institutions in favor of the demands of the field of nursing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Analyzing the objects of study of the selected articles, it was found that, in the Brazilian context, ABEn was the focus of most of the studies, perhaps because it is the oldest nursing organization in the country, and even acts as an umbrella organization for other municipal, union, and scientific nursing organizations in Brazil (9,11,14) . It seems that, in a way, all of the articles addressed the contributions of the Association to the world of nursing, especially in the areas of education (15)(16) , care and professional practice (14,(17)(18) , political participation (19) , and preservation of the memory of the profession (13) . It is noteworthy that there was mention of unions, specialties, and supervisory bodies of professional nursing practice during the joint work developed by these institutions in favor of the demands of the field of nursing.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing all of the proposed objectives and methodological approaches used together, it was possible to perceive that the selected articles sought mainly to describe the contributions of the organizations to the development of the profession. As such, the descriptive methodology, historical and social studies, and theoretical reflective discursive studies were those best adapted to this purpose (9)(10)(11)(13)(14)(15)(17)(18)(19)(20) . This is possibly because these types of research enable description of objects of study related to the phenomenon of the social and political participation of nursing, as well as discussing their situational aspects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Os profissionais são reconhecidos por desenvolverem um trabalho útil à sociedade, organizam-se em entidades de representatividade social, que estabelecem regras para o exercício da profissão e um código de ética que orientem suas ações (Albuquerque, 2006).…”
Section: Discutindo Critérios Justos No Corte De Pessoal Por Redução unclassified